The Transcriptional Regulators of the CRP Family Regulate Different Essential Bacterial Functions and Can Be Inherited Vertically and Horizontally - Soberón-Chávez, Gloria; Alcaraz, Luis D.; Morales, Estefanía; Ponce-Soto, Gabriel Y.; Servín-González, Luis (Frontiers in Microbiology, 2017)
One of the best-studied transcriptional regulatory proteins in bacteria is the Escherichia coli catabolite repressor protein (CRP) that when complexed with 3’-5’-cyclic AMP (cAMP) changes its conformation and interacts with specific DNA-sequences. CRP DNA-binding can result in positive or negative regulation of gene expression depending on the position of its interaction with respect to RNA polymerase binding site. The aim of this work is to review the biological role and phylogenetic relations that some members of the CRP family of transcriptional regulators (also known as cAMP receptor protein family) have in different bacterial species. This work is not intended to give an exhaustive revision of bacterial CRP-orthologs, but to provide examples of the role that these proteins play in the expression of genes that are fundamental for the life style of some bacterial species. We highlight the conservation of their structural characteristics and of their binding to conserved-DNA sequences, in contrast to their very diverse repertoire of gene activation. CRP activates a wide variety of fundamental genes for the biological characteristic of each bacterial species, which in several instances form part of their core-genome (defined as the gene sequences present in all members of a bacterial species). We present evidence that support the fact that some of the transcriptional regulators that belong to the CRP family in different bacterial species, and some of the genes that are regulated by them, can be inherited by horizontal gene transfer. These data are discussed in the framework of bacterial evolution models.